The Effect of Nutrition Education “Booklet Mahir Gizi Olahraga (BOMAZIGA)” on Knowledge and Attitudes of Football Athletes in Palembang - Arafah, Fadhilah Nur; Purnama Sari, Indah; Fitri Arinda, Ditia (Universitas PGRI Palembang, 2025)
Abstract Currently, sports performance in Indonesia, especially in football, remains unstable, with fluctuations in performance. One of the contributing factors to this decline is inadequate knowledge and attitudes regarding dietary patterns and nutritional status, which can negatively effect athletes' performance and consequently their achievements. Therefore, preventive efforts are needed, such as nutrition education that involves and stimulates curiosity through BOMAZIGA (Booklet Mahir Gizi Olahraga). This study aims to investigate the effect of nutrition education through the BOMAZIGA game on the knowledge and attitudes of football athletes in Palembang City.The research method used was a Quasi-Experimental design with a pre-test post-test control group approach, involving 80 respondents, consisting of 40 participants in the treatment group and 40 in the control group. Purposive sampling was employed to select the sample. The variables studied were knowledge and attitudes based on pre-test and post-test scores. The effect analysis was conducted using the Wilcoxon test and Mann-Whitney test. The results of the study indicated a significant improvement in knowledge about dietary patterns and nutritional status by 95.2% and a positive attitude improvement of 81% after the intervention. The Wilcoxon test for knowledge and attitudes showed p = 0.000 (p < 0.05), indicating a significant difference before and after the intervention. The Mann-Whitney test showed p = 0.000 (p < 0.05), suggesting that nutrition education using the BOMAZIGA media had an effect on both knowledge and attitudes of athletes. The BOMAZIGA game proved to be an effective tool for improving knowledge and attitudes regarding dietary patterns and nutritional status, making it an efficient educational medium for delivering information to athletes. Keywords: Football Athletes, Nutritional Education, Knowledge, Attitudes, Booklet